2011
DOI: 10.1001/jama.2011.620
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Closures of Emergency Departments in the United States

Abstract: Context Between 1998 and 2008, the number of hospital-based emergency departments (EDs) in the United States declined, while the number of ED visits increased, particularly visits by publicly-insured and uninsured patients. Little is known about the hospital, community, and market factors associated with ED closures. Federal law requiring EDs to treat all in need regardless of a patient’s ability to pay may make EDs more vulnerable to the market forces that govern US health care. Objective To determine hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(163 citation statements)
references
References 40 publications
(44 reference statements)
4
155
1
1
Order By: Relevance
“…While Kangovi and colleagues74 also identified patients of low socioeconomic status prefer hospital care over primary care because they view it as more convenient and accessible whilst also providing higher quality care for less cost. A study about ED closures by Hsia et al 75. found that ED closures disproportionately affected vulnerable communities, for example, those without medical insurance, minority groups, or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…While Kangovi and colleagues74 also identified patients of low socioeconomic status prefer hospital care over primary care because they view it as more convenient and accessible whilst also providing higher quality care for less cost. A study about ED closures by Hsia et al 75. found that ED closures disproportionately affected vulnerable communities, for example, those without medical insurance, minority groups, or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, increases in uncompensated care, low profit margins, and location in high-poverty areas have resulted in the closure of emergency departments or even entire hospitals. 28 For example, in 2011 the Cleveland Clinic decided to close Huron Hospital because of financial losses; the hospital served an impoverished, primarily black population in East Cleveland. 29 Further erosion of the hospital safety net could also exacerbate other problems such as availability of and access to specialty and inpatient referrals.…”
Section: Timeline For Reformmentioning
confidence: 99%
“…In recent years, EDs in the United States have seen a near thirty million patient per year increase in volume. During the same time period, approximately a third of urban area EDs were closed [3]. In the U.S. health care system, hospital emergency departments are unique in their legal obligation to treat all patients in need, without regard for their ability to pay.…”
Section: Introductionmentioning
confidence: 99%